Intercropping impact on population of cotton sucking insect pests - DEVI, SUMAN; RAM, PALA; ROLANIA, KRISHNA (The Indian Journal of Agricultural Sciences, 2021)
The cotton intercropping experiment was conducted for the management of sucking pests, viz. leafhopper, Amrasca biguttula biguttula Ishida (Hemiptera: Cicadellidae); whitefly, Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) and thrips, Thrips tabaci Linderman (Thysanoptera: Thripidae) in desi cotton, Gossypium arborium. The results of the study revealed that less mean population of leafhopper nymphs, whitefly and thrips adults was recorded from the treatments T7 (2.47, 2.61 and 2.10/leaf, respectively) and T8 (2.49, 2.52 and 2.25/leaf, respectively) where pearl millet (Pennisetum glaucum L.) and sorghum (Sorghum bicolor L.) crops grown as border crops around cotton, respectively. Cotton as sole crop (T9) recorded the highest mean population of leafhopper nymphs, whitefly and thrips adults i.e. 3.54, 3.97, 3.59/leaf, respectively. However, the maximum net returns was recorded in cotton intercropped with sesame 1:1 (T1: 104140 `/ha) whereas minimum net returns was recorded in sole cotton (T9: 80021 `/ha).